2023
DOI: 10.1111/ijfs.16548
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of fish gelatin and red pitaya peel powder edible film production

Rizka Aulia Rahma,
Widya Dwi Rukmi Putri,
Atanasia Adventina Megatri
et al.

Abstract: SummaryGrowing awareness of the environmental devastation caused by plastic packaging, particularly in the food industry, has led to the emergence of the concept of a renewable and environmentally safe consumable film as an alternative to plastic. Red pitaya (dragon fruit) peel (RPP), which has a high pectin content, can be used as an additional ingredient or co‐biopolymer to enhance the functional properties of fish gelatin (FG) edible film. Edible films were produced using casting techniques and varying conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Peak ~1650 cm -1 explained as C=O stretching and H2O bending [46][47]57]. According to Rahma et al, the wavenumber area 500-1500 shows the fingerprint area which shows a signature peak that confirms the formation of bonds at the preceding wavenumber (2000-4000cm) [58]. In Fig.…”
Section: Ftirmentioning
confidence: 87%
“…Peak ~1650 cm -1 explained as C=O stretching and H2O bending [46][47]57]. According to Rahma et al, the wavenumber area 500-1500 shows the fingerprint area which shows a signature peak that confirms the formation of bonds at the preceding wavenumber (2000-4000cm) [58]. In Fig.…”
Section: Ftirmentioning
confidence: 87%
“…Red pitaya is colourful and considered better tasting, making it the most popular among consumers. 2 Previous studies have confirmed that pitaya is rich in a variety of active ingredients such as fatty acids, flavonoids, and polyphenols, with a higher content of betaine, 3,4 pectin, 5 etc . In addition, these chemical components have significant anti-oxidant, anti-diabetic activity, 6,7 and other activities.…”
Section: Introductionmentioning
confidence: 96%
“…(2023) study addresses the challenges faced by the global food system and provides actionable insights and methodologies to guide researchers and industry stakeholders in creating a more sustainable and secure future for food production and consumption. Optimization of fish gelatin and red pitaya peel powder edible film production—Rahma et al . (2023) research investigates the production of edible films using fish gelatine and red pitaya peel powder, offering potential alternatives to plastic packaging with desirable functional properties. Influence of amino acid profiles and secondary structure on nutritional and functional properties of Trichilia emetica and Trichilia dregeana proteins—Tsomele et al . (2023) study explores the potential of proteins from Trichilia oilseeds, traditionally used in underutilised tree seeds, to address protein malnutrition in economically disadvantaged communities. Alternative proteins as fish meal substitution in diets for largemouth bass (Micropterus salmoides): a mini‐review—Cheng et al .…”
mentioning
confidence: 99%
“…Optimization of fish gelatin and red pitaya peel powder edible film production—Rahma et al . (2023) research investigates the production of edible films using fish gelatine and red pitaya peel powder, offering potential alternatives to plastic packaging with desirable functional properties.…”
mentioning
confidence: 99%